An Analysis of the Work Ethic of Religious Education Teachers in Increasing Student Learning Motivation at Darul Muttaqin Integrated Islamic Middle School - Yayuk Safitri; Puji Wahyuningsih; Nida Wahyu Husna; Siti Halimah; Yeni Yulianti; Imam Sayuti; M. Iqbal Azmi Al Latif; Hiyarotus Sulaimah; Isna Harisa Hasanah; Ata Zamzami Mubarok (CV. Creative Tugu Pena, 2022)
This study aims to analyze the work ethic of Islamic Education (PAI) teachers in enhancing students' learning motivation at SMP Islam Terpadu Darul Muttaqin Rumbia, Central Lampung Regency. The background of this research highlights the crucial role of teachers in fostering effective learning environments and encouraging high student motivation. A descriptive qualitative approach was employed, utilizing data collection methods such as observation, interviews, and documentation. The research subjects included the school principal, PAI teachers, and eighth-grade students. The findings reveal that a strong teacher work ethic—reflected in time discipline, mastery of subject matter, teaching creativity, and a strong sense of responsibility—significantly contributes to increased student motivation. However, several challenges remain, such as teacher tardiness, limited creativity in delivering material, and weak content mastery. Therefore, continuous improvement of teachers' work ethic is essential to support the achievement of optimal educational outcomes. Keywords : Work Ethic, Religious Education Teachers, Learning Motivation